Field-ground reversal in Islamic art as a model for confronting indeterminancy in theology - Johnston, William M. (Sophia, 2003)
Field-ground reversal underlies Islamic art's use of repeating geometric patterns or tessellations. Encounter with field-ground reversal suggests the notion of ‘oscillationism’ to mean willingness to oscillate between two equally plausible opposites rather than to affirm one or the other of them. This article explores oscillationism as a move for confronting theories of evil and for assessing the merits of foundationalism without succumbing to cognitive dissonance. The article goes on to examine F.D.E. Schleiermacher's suggestion of 1799 that the infinitude of God calls for more, not fewer religions. His reversal of Christian and Muslim assumptions puts contemporary debate in the theology of religions into a postmodernist perspective. Without supplying fresh answers, the spiritual practice of oscillationism provides a fresh way to frame some of the weightiest questions.